Why kids kill parents child abuse and adolescent homicide - Heide, Kathleen M.; Sage eBooks (Thousand Oaks, Calif. : SAGE, 1995)
Criminologist and psychotherapist Kathleen Heide focuses on families that breed violence and the relationship between patricide and child abuse. A discussion of maltreatment, who kills, youths at risk, and legal and psychological issues is followed by three detailed case studies and a discussion of intervention, society's contributions to both the.
Originally published: Columbus : Ohio State University Press, 1992.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Parricide -- United States; Dysfunctional families -- United States; Family violence -- United States; Adolescent psychotherapy -- United States; Electronic books